Effect of oral rose-water on cervical ripening in primiparous women - Sedigheh Shariat Moghani; Reihaneh Jarrahi; Maryam Moradi; Hasan Rakhshande; Jamshid Jamali; Elham Esform (Majallah-i Zanān, Māmā̓ī va Nāzā̓ī-i Īrān, 2021)
Introduction: Cervical ripening and induction of labor is necessary before the spontaneous onset of labor. In traditional medicine, rose-water has been used as an effective factor in the onset of labor contractions. However, clinical studies on its efficacy are very rare. This study was performed with aim to determine the effect of oral rose-water on cervical ripening in primiparous women. Methods: This randomized clinical trial study was performed in 2019 on 60 primiparous women with 40 weeks of gestation in the maternity of Tabas hospital. The subjects were assigned to two groups of intervention and control (n=30 in each group). The intervention group consumed five ml of oral rose-water daily since 40 week of gestation for one week and the control group received routine care. Bishop score was measured at days one, three, seven and entering the labor. Data collection tools were the forms of questionnaire, physical examination, observation and counting fetal movement and the checklist of rose-water consumption. Data were analyzed using T-tests, Chi-square, and analysis of variance with repeated measures. P<0.05 was considered statistically significant. Results: The mean age of mothers in the intervention and control groups was 26.53± 5.16 and 26.53± 5.28, respectively. The onset of labor did not show a significant difference in two groups (p=0.303). Analysis of variance with repeated measures showed that the mean of Bishop score on the third and seventh days after beginning of the intervention was not significantly different between the two groups (p =0.160). The results of this test showed that the trend of bishop score changes in both groups was incremental. Conclusion: According to the results of the study, daily consumption of 5 ml rose-water (with concentration of 24% rose water essential), had no significant effect on cervical ripening in primiparous women had no side-effects. It is recommended that future research be done with higher dose of rose-water with safe dose range on cervical ripening.